High‐Definition City: An Invisible Horizon of Technological Human Space. (3rd January 2023) - Lu, Andong; Burry, Jane; White, Marcus
Abstract: Guest‐Editors Jane Burry and Marcus White team up with Andong Lu, Lead Professor in Urban Design and Vice‐Dean of the School of Architecture and Urban Planning at Nanjing University, to explore the ups and downs of our contemporary condition relative to the exponential rise in the seamlessness of technology – particularly digital technology. This is a complex arena that is both liberating yet can also be invasive to our privacy and dignity, presenting a paradox that they here attempt to unravel for us.